Collaboration of Actor Networks From The Hexa Helix Perspective in Tourism Development at The Buthak Mountain Climbing Base Camp - Panderman Batu City - Hendra Riskianto; Muhamad Rifa'i; Warter Agustim (International Research & Development for Human Beings (IRDH), 2026)
This study aims to assess the degree of collaboration between each elemental Hexa Helix and identify factors that support and inhibit tourism development at the Buthak Mountain Climbing Basecamp - Panderman, Batu City. This type of research is descriptive with a qualitative approach. A purposive sampling technique was used to determine the informant group, consisting of the Perhutani government, PT. Manggala Teknologi Nusantara as an investor, Tribhuwana Tunggadewi University Malang as an academic, the Tuyomerto Forest Village Community Institution, the Public Relations department of Buthak Mountain Climbing Basecamp - Panderman, and the Affected Community as consumers and tourists. Data analysis using the Miles, Huberman, and Saldana 2014 method consists of data collection, condensation, presentation, and conclusion. The results of the collaborative research of the network of actors with a hexa helix perspective in tourism development in Mount Buthak - Panderman, Batu City, involve many parties, such as the government represented by Perhutani as the conception, manager, and regulator of various policies, PT Manggala Teknologi Nusantara as an investor who makes investments, the Tribhuwana Tunggadewi University of Malang represented by the Dean of the Faculty of Economics as an academic, Community Institutions represented by LMDH Tuyomerto, Basecamp Public Relations as the media, and Ignasius Reza Hernando as consumers and tourists who visit Mount Buthak - Panderman, Batu City. The six actors fulfill all the elements of Hexa Helix. Each actor plays their respective roles and collaborates well in developing tourism in Gunung Buthak - Panderman, Batu City. Supporting factors include the involvement of each element of Hexa Helix and the full support of the local government and management.